Comparative analysis of online stores - Wójtowicz, Arkadiusz; Miłosz, Marek (Journal of Computer Sciences Institute, 2021)
This article raises issues of online stores. An analysis of many aspects of sales platforms was carried out, such as awareness of these platforms, frequency of purchases, assessment of interface quality, intuitiveness, safety and their popularity. Allegro, Amazon, Aliexpress, Ebay and Wish were selected from the most popular online stores.. In addition, a survey conducted and properly analysed, which examines the awareness and experiences of users related to online stores. This article allowed us to draw relevant conclusions about these sales platforms and their community